Variance in Anterior Cruciate Ligament Reconstruction Graft Selection based on Patient Demographics and Location within the Multicenter Orthopaedic Outcomes Network Cohort - Houck, Darby A.; Kraeutler, Matthew J.; Vidal, Armando F.; McCarty, Eric C.; Bravman, Jonathan T.; Wolcott, Michelle L.; MOON Knee Group; Amendola, Annunziato; Andrish, Jack T.; Brophy, Robert H.; Dunn, Warren R.; Flanigan, David C.; Huston, Laura J.; Jones, Morgan H.; Kaeding, Christopher C.; Marx, Robert G.; Matava, Matthew J.; McCarty, Eric C.; Parker, Richard D.; Spindler, Kurt P.; Wolcott, Michelle L.; Wolf, Brian R.; Wright, Rick W.; Vidal, Armando F. (The Journal of Knee Surgery, 2018)
The purpose of this study is to determine whether any regional or age-related patterns exist in graft choice for patients undergoing primary anterior cruciate ligament reconstruction (ACLR) within a large multicenter consortium. A retrospective cohort study was performed using data collected from the Multicenter Orthopaedic Outcomes Network (MOON) on patients having undergone primary ACLR. Patients were stratified by age group (younger than 20, 20–29, 30–39, 40–49, and 50+ years) and four demographic regions (Midwest, Southeast, Northeast, and West). A total of 2,149 patients (1,288 males, 861 females) were included. At least 70% of the patients were treated by a single surgeon in three of the four demographic regions. There were no clinically significant differences in body mass index (BMI), and no statistically significant differences in Marx activity rating scale (p > 0.05) between regions within any particular age group. There were significant differences in the proportion of autografts versus allografts used for primary ACLR between regions in every age group (p < 0.01). There were also significant differences in autograft (p < 0.001) and allograft (p < 0.001) harvest location based on demographic region. The Southeast and Northeast were more likely to use bone-patellar-tendon-bone autograft while the West and Midwest were likely to use hamstring autograft. Within our consortium, regional patterns exist both in autograft versus allograft use in patients undergoing primary ACLR, as well as harvest location of autografts and allografts. Given the similarities in average patient BMI and activity level between regions, as well as the single surgeon influence in three of the four regions, the regional patterns in graft use are likely due to surgeon preference.
Keywords: anterior cruciate ligament reconstruction; allograft; autograft; demographics